Statistics without mathematics - Bartholomew, David J. (Sage Publications, 2016)
"An ideal primer for students who need an introduction to the concepts of statistics without the added confusion of technical jargon and mathematical language. It introduces the intuitive thinking behind standard procedures, explores the process of informal reasoning, and uses conceptual frameworks to provide a foundation for students new to statistics. It showcases the expertise we have all developed from living in a data saturated society, increases statistical literacy and offers the tools needed to approach statistical mathematics with confidence"--Back cover.